Instrumental delivery and ultrasound: a multicentre randomised controlled trial of ultrasound assessment of the fetal head position versus standard care as an approach to prevent morbidity at instrumental delivery - Ramphul, Meenakshi; Ooi, Poh Vei; Burke, Gerard; Kennelly, Mairead M.; Said, Soha A.T.; Montgomery, Alan A.; Murphy, Deidre J. (Wiley, 2014)
Objectives: To determine whether the use of ultrasound can reduce the incidence of incorrect diagnosis of the fetal head position at instrumental delivery and subsequent morbidity.